An assessment of the future of tourism in Salenrang Tourism Village, Maros Regency - Mappasomba, Zulkifli; Nurhidayat, M.; Awaluddin , Iyan; Nurhidayat, Nurhidayat; Amri, Armin (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
This study aims to measure the level of tourism sustainability through community perceptions, and identify factors that influence future-orientated sustainability, as well as select the best strategy for long-term management. This was done because in Salenrang Village, Maros Regency, since it was established as a nature tourism destination in 2007, it has also absorbed labour, such as community involvement in management and local businesses. However, the surge in tourist flows has not fully prospered the local community, besides potentially causing ecological damage, degradation of natural quality, and conflicts of interest between stakeholders. This research uses quantitative and qualitative approaches. Quantitative data from the questionnaire survey, while qualitative data were obtained from in-depth interviews, document analysis and literature study. SOAR analysis was used to assess strategic factors and design future tourism management concepts. The results showed that overall, the natural tourism area of Salenrang Village has a fairly good indication of maintaining sustainability with the institutional dimension rated the strongest. However, there are several dimensional indicators that need further attention, such as waste management, increasing community income, and increasing knowledge about sustainable tourism. The SOAR analysis revealed strategic formulations to maintain its sustainability, such as the utilisation of community participation, the development of local creative industries, and educational programmes to be applied in maintaining its long-term sustainability, so that it becomes a guide for local governments, tourism managers, and other related parties in developing sustainable tourism management models based on community participation.